2006
DOI: 10.1103/physrevlett.97.118102
|View full text |Cite
|
Sign up to set email alerts
|

Does the1/fFrequency Scaling of Brain Signals Reflect Self-Organized Critical States?

Abstract: Many complex systems display self-organized critical states characterized by 1/f frequency scaling of power spectra. Global variables such as the electroencephalogram, scale as 1/f, which could be the sign of self-organized critical states in neuronal activity. By analyzing simultaneous recordings of global and neuronal activities, we confirm the 1/f scaling of global variables for selected frequency bands, but show that neuronal activity is not consistent with critical states. We propose a model of 1/f scalin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
337
3
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 370 publications
(388 citation statements)
references
References 28 publications
43
337
3
1
Order By: Relevance
“…This result is in agreement with observations from neuronal dynamics in cat association cortex ( Fig. 2C; Bedard et al, 2006). This provides evidence that the experimental observations of Poisson dynamics (exponential ISI distributions) and absence of avalanche dynamics, are all consistent with self-generated irregular states in cortical networks.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This result is in agreement with observations from neuronal dynamics in cat association cortex ( Fig. 2C; Bedard et al, 2006). This provides evidence that the experimental observations of Poisson dynamics (exponential ISI distributions) and absence of avalanche dynamics, are all consistent with self-generated irregular states in cortical networks.…”
Section: Discussionsupporting
confidence: 92%
“…7, right). These data show that the apparent Poisson statistics and absence of avalanche dynamics observed in cat association cortex (Bedard et al, 2006) is also found in network models.…”
Section: Comparison Of Models To Experimental Datasupporting
confidence: 61%
See 2 more Smart Citations
“…Consequently, for most combinations of parameters the number of firing neurons is an almost constant but noisy time series. This is in correspondence with the behaviour of the real brain: it is a commonplace in neuroscience that electroencephalograms (EEG) are noisy signals with a spectrum 1/f which has been associated with self-organized criticality [47] although, in the case of the brain, that explanation has been dismissed [48]. On the other hand, in some clinical cases, a regular synchronous oscillation appears.…”
Section: The Phase Diagrammentioning
confidence: 99%